Severe Inflammatory Ophthalmopathy in a Euthyroid Patient during Nivolumab Treatment. Issue 2 (4th March 2018) - Campredon, Pauline; Imbert, Philippe; Mouly, Céline; Grunenwald, Solange; Mazières, Julien; Caron, Philippe
Abstract : Introduction: Nivolumab is a promising treatment in patients with advanced malignancies. Among immune-related adverse events, autoimmune thyroid disorders are frequently reported. Patient: A 61-year-old male patient had no history of familial or personal thyroid disease. In 2012, this patient, a heavy smoker, presented with non-small-cell lung cancer that was treated with radiotherapy and chemotherapy. In 2015, the cancer progressed with cervical compressive symptoms, and the patient was treated with nivolumab. Results: After 3 infusions, bilateral eyelid ptosis and bilateral conjunctival redness with chemosis were observed. Ophthalmologic examination revealed severe proptosis with complete ophthalmoplegia but with normal vision, color test, and optic disk. Thyroid function tests were normal (TSH = 0.65 mU/L, free T4 = 15.4 pmol/L) without anti-thyroperoxidase or anti-TSH receptor antibodies. CT scan of the orbits confirmed marked bilateral proptosis with expansion of the orbital adipose tissue without significant thickening of extraocular muscles. T2-weighted MRI showed inflammation of orbital adipose tissue. Nivolumab treatment was withdrawn, and the patient received weekly intravenous high-dose methylprednisolone (1 g for 2 weeks, 500 mg for 4 weeks, and 250 mg for 5 weeks). After the first 3 cycles, significant improvement of left chemosis was observed whereas bilateral ptosis and ophthalmoplegia were unchanged. The patient was euthyroid without thyroid autoimmunity 1 week prior to his death due to massive hemoptysis. Conclusion: We report severe inflammatory ophthalmopathy in a euthyroid patient with non-small-cell lung cancer during nivolumab therapy. The occurrence of such ophthalmic adverse events is likely to increase during nivolumab therapy in patients with advanced malignancies.